E-COMMERCE ON THE SUCCESS OF MICRO, SMALL AND MEDIUM ENTERPRISES - A Riyanto; M Khairi; R H Asmara; H Saputra (FIRM Journal of Management Studies, 2021)
This study aims to analyze the role of e-commerce in business success in the meta-measure path. E-Business is a new business model that provides significant benefits such as savings in the cost of fast execution of business transactions and encourages the globalization of business activities, thereby removing barriers to market penetration. E-Business is developed in large companies and creates in Micro, Small, and Medium Enterprises (SMEs). Small and Medium Enterprises (SMEs) are an essential part of a country or region's economy, including Indonesia. The method used is a qualitative analysis method with case studies. This study uses four micro-scale entrepreneurs who use e-commerce in carrying out their business activities as research objects. The analysis process is carried out based on e-commerce in Small and Medium Enterprises (SMEs) in Bandung. This picture is obtained through direct interviews with the object of research. Based on the study results, it can be concluded that, in general, e-commerce has a role that can help uses four micro-scale entrepreneurs in improving their business development. The results of the analysis also explain that the four micro-scale entrepreneurs persist in using e-commerce.